Anterolateral congenital tibial bowing: case report - Mastantuoni, Giuseppe; Aulisa, Angelo Gabriele; Giordano, Marco; Savignoni, Pietro; Toniolo, Renato Maria; Falciglia, Francesco (Frontiers in Pediatrics, 2023)
Abstract: Backround: The treatment of congenital curvatures (bowing) of the tibia still represent a challenging problem for all Paediatric Orthopaedic Surgeons because of its unpredictable course especially if pseudoarthrosis occurs after a pathologycal fracture of the tibia. Case presentation: We describe a case of a child affected by an isolated curvature of his left leg. The congenital malformation was discovered at birth and any other pathological clinical finding was present. The first X-Ray showed the presence of a congenital curvature of the tibia of the antero-lateral type. Surgery consisted on a double osteotomy, both of the fibula and of the tibia. Subtraction of the distal metadiaphyseal portion of the fibula and tibial osteotomy in correspondence of the major curvature (antero-lateral) convexity and stabilized then by an internal endo-midollary Rush rod inserted proximally to the tibia, under the cartilage growth plate and made it end inside the distal tibial epiphysis, through out the distal tibial cartilage growth plate, preserving the ankle joint. Results: The patient had immediately an excellent outcome. The tibial osteotomy site healed perfectly. The child was found, at periodical orthopaedic follow up visits, always better. Any clinical significative evidence of growth disturbances, do to the Rush rod that crossed the distal tibial cartilage growth plate, were noted. Rather, X-rays showed that the Rush rod progressively mooved upwards together with the tibial bone growth, getting always more far away from the distal tibial cartilage growth plate. Moreover, even the leg discrepancy and the pelvic obliquity improved. After an 8 year follow up, the patient, now 11 years and a ½ young boy, has an excellent outcome. Conclusions: Our case report for sure adds other important information for the treatment of these rare congenital disorders. In particular it highlights the management of a “pre-fracture stage” in a severe congenital tibial antero-lateral curvature in a very young child and describes the surgical technique performed.